A hemodynamic-directed approach to pediatric cardiopulmonary resuscitation (HD-CPR) improves survival. (February 2017) - Morgan, Ryan W.; Kilbaugh, Todd J.; Shoap, Wesley; Bratinov, George; Lin, Yuxi; Hsieh, Ting-Chang; Nadkarni, Vinay M.; Berg, Robert A.; Sutton, Robert M.; ,
Abstract: Aim: Most pediatric in-hospital cardiac arrests (IHCAs) occur in ICUs where invasive hemodynamic monitoring is frequently available. Titrating cardiopulmonary resuscitation (CPR) to the hemodynamic response of the individual improves survival in preclinical models of adult cardiac arrest. The objective of this study was to determine if titrating CPR to systolic blood pressure (SBP) and coronary perfusion pressure (CoPP) in a pediatric porcine model of asphyxia-associated ventricular fibrillation (VF) IHCA would improve survival as compared to traditional CPR. Methods: After 7 min of asphyxia followed by VF, 4-week-old piglets received either hemodynamic-directed CPR (HD-CPR; compression depth titrated to SBP of 90 mmHg and vasopressor administration to maintain CoPP ≥20 mmHg); or Standard Care (compression depth 1/3 of the anterior–posterior chest diameter and epinephrine every 4 min). All animals received CPR for 10 min prior to the first defibrillation attempt. CPR was continued for a maximum of 20 min. Protocolized intensive care was provided to all surviving animals for 4 h. The primary outcome was 4-h survival. Results: Survival rate was greater with HD-CPR (12/12) than Standard Care (6/10; p = 0.03). CoPP during HD-CPR was higher compared to Standard Care (point estimate +8.1 mmHg, CI95 : 0.5–15.8 mmHg; p = 0.04). Chest compression depth was lower with HD-CPR than Standard Care (point estimate −14.0 mm, CI95: −9.6 to −18.4 mm; p < 0.01). Prior to the first defibrillation attempt, more vasopressor doses were administered with HD-CPR vs. Standard Care (median 5 vs. 2; p < 0.01). Conclusions: Hemodynamic-directed CPR improves short-term survival compared to standard depth-targeted CPR in a porcine model of pediatric asphyxia-associated VF IHCA.